Skrining Tekanan Darah Sebagai Langkah Preventif Komplikasi Hipertensi Pada Masyarakat Desa Kasemen, Provinsi Banten: Blood Pressure Screening as a Preventive Effort to Reduce Hypertension Complications in Kasemen Village Community, Banten Province - Adhayati, Baety; Prameswari, Yuda Nabella; Hermawati, Luluk; Wulansari, Ekawati Rini; Zulfa, Hilizza Awalina; Putri, Neshya Ruriana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Hypertension is a non-communicable disease that is a leading cause of global morbidity and mortality. In Indonesia, the prevalence of hypertension continues to rise, particularly among the productive and elderly populations. This community service activity aims to conduct early detection and provide education on hypertension through blood pressure screening in Kasemen Village, Serang City, Banten Province. The method employed is a participatory approach involving faculty members and medical students from the Faculty of Medicine and Health Sciences at UNTIRTA. A total of 247 village residents participated in this activity, and from 230 valid data, it was found that 51.30% of respondents had hypertension. The highest proportion of hypertension was observed among the elderly group (71.6%) and men (80%). In addition to blood pressure measurement, education on the importance of regular blood pressure monitoring and healthy lifestyle changes was also provided to raise community awareness. The results of this activity demonstrate that community-based screening, combined with health education, is an effective strategy for preventing and controlling hypertension, while also serving as a field-based learning opportunity for medical students.